2013
DOI: 10.1517/14656566.2014.868885
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin – something new for type 2 diabetes, but is it safe and efficacious?

Abstract: Studies with canagliflozin, in subjects with type 2 diabetes, have shown that its use is associated with reductions in HbA1c and body weight and small reductions in blood pressure and triglycerides, while increasing high-density lipoprotein cholesterol and low-density lipoprotein cholesterol. As monotherapy in Japanese subjects, or in comparison with glimepiride in CANTATA-SU (CANagliflozin Treatment and Trial Analysis versus SUlphonylurea), canagliflozin causes a low incidence of hypoglycemia, and this is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It was thought to be due to increased urinary glucose which may act as a potential fungal growth factor in SGLT2-i treated patients (32). These studies have raised concerns about the safety testing of SGLT2-i with regards to the higher incidence of genital infections (33,34). We didn't find the higher risk of urinary tract infection in SGLT2-i plus metformin compared with metformin monotherapy.…”
Section: Discussionmentioning
confidence: 87%
“…It was thought to be due to increased urinary glucose which may act as a potential fungal growth factor in SGLT2-i treated patients (32). These studies have raised concerns about the safety testing of SGLT2-i with regards to the higher incidence of genital infections (33,34). We didn't find the higher risk of urinary tract infection in SGLT2-i plus metformin compared with metformin monotherapy.…”
Section: Discussionmentioning
confidence: 87%
“…A randomized, doubled-blind placebo-controlled study to examine the safety and tolerability of canagliflozin indicated upper respiratory tract infection as adverse effects reported in over 3% of patients [35]. Federal Drug Administration (FDA) has recently approved canagliflozin for use in type 2 diabetes, while directing that a clinical outcome safety trial be undertaken [36]. Dual SGLT1/SGLT2 inhibitors, such as canagliflozin [37] and LX4211 [38], have been introduced in the diabetes pharmacopeia; however, bronchial inflammation, airway damage and reduction of survival rate should be considered in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Such observations have raised concerns about the safety testing of SGLT2 inhibitors with regards to the higher incidence of genital infections. [37,38] …”
Section: Discussionmentioning
confidence: 99%